Hypoxia-Derived Mesenchymal Stem Cell Exosomes Downregulate CXCL12 and Upregulate IL-10 Expression in a Murine Model of Androgenic Alopecia - Denawati Denawati; Eko Setiawan; Sri Priyantini (Molecular and Cellular Biomedical Sciences, 2026)
Background: Androgenic alopecia (AGA) is characterized by hair follicle miniaturization and chronic inflammation mediated by dihydrotestosterone (DHT). Current therapies primarily target hormonal pathways and do not adequately address inflammatory dysregulation. Exosomes derived from hypoxia-conditioned mesenchymal stem cells (EH-MSCs) exhibit enhanced immunomodulatory properties. However, their effects on key inflammatory mediators in AGA remain unclear. This study evaluated the effects of EH-MSCs on CXCL12 and IL-10 expression in a DHT-induced AGA mouse model.Materials and methods: Male C57BL/6 mice were allocated into five groups: healthy control, DHT-induced alopecia without treatment, DHT-induced alopecia treated with topical minoxidil, and EH-MSCs administered at 100 or 200 µL/kgBW. Alopecia was induced by subcutaneous DHT injection for 17 days. Following model validation, treatments were administered on days 25 and 32. CXCL12 and IL-10 expression in dorsal skin tissue was analyzed using RT-PCR on day 39.Results: DHT induction significantly increased CXCL12 expression and reduced IL-10 levels (p<0.05). EH-MSC administration dose-dependently downregulated CXCL12 (1.73±0.57 and 1.54±0.44 fold-change) and upregulated IL-10 expression (3.10±0.75 and 3.29±0.67 fold-change), demonstrating greater immunomodulatory effects compared with minoxidil.Conclusion: EH-MSCs effectively modulated inflammatory biomarkers by suppressing CXCL12 and enhancing IL-10 expression in a DHT-induced AGA model, suggesting their potential as an immunoregenerative therapeutic strategy for androgenic alopecia.Keywords: androgenic alopecia, mesenchymal stem cells, exosomes, hypoxia, CXCL12, IL-10